Pengaruh Word of Mouth, Kesadaran Merek dan Kualitas Produk Terhadap Keputusan Pembelian Pada Marketplace Blibli di Kota Batam - David David; Hikmah Hikmah (LPPM Universitas Putera Batam, 2026)
This research was conducted to analyze the influence of Word of Mouth, Brand Awareness and Product Quality on purchase decision on e-commerce Blibli, both partially and simultaneously. The sample for this research consisted of 204 respondents selected using a non-probability sampling technique, with data collected through questionnaires. Data processing was carried out using SPSS version 29, which included data quality test, classic assumption test, influence analysis, and hypothesis test using multiple linear regression methods to examine the effect of independent variables on the dependent variable. The results of the study indicate that word of mouth does not have a significant influence on purchase decisions. Brand awareness, and product quality each have a significant positive influence on purchase decision, Simultaneously, word of mouth, brand awareness and product quality have a positive and significant influence on purchasing decisions. The result of this result can be used to contribute to the future development of Blibli's e-commerce platform.